Arsenic adsorption from aqueous solutions by activated red mud - Altundoğan, Hamdi Soner; Altundoğan, Sema; Tümen, Fikret; Bildik, Memnune (My University, 2002)
Heat treatment and acid treatment methods have been tested on red mud to increase its arsenic adsorption capability. The results indicate that the adsorptive capacity of red mud can be increased by acid treatment. This treatment causes sodalite compounds to leach out. As(III) and As(V) adsorption characteristics of activated red mud have similar tendencies with raw red mud. Batch adsorption studies have shown that activated red mud in dosages ranging from 20 to 100 g l?1 can be used effectively to remove arsenic from aqueous solutions. The process is pH dependent, the optimum range being 5.8–7.5 for As(III) and 1.8–3.5 for As(V). The maximum removals are 96.52% for As(V) and 87.54% for As(III) for solutions with a final pH of 7.25 and 3.50, respectively, for the initial arsenic concentration of 133.5 ?mol l?1 (10 mg l?1), activated red mud dosage of 20 g l?1, contact time of 60 min and temperature of 25 °C. The adsorption data obtained follow a first-order rate expression and fit the Langmuir isotherm well. Isotherms have been used to obtain the thermodynamic parameters. It was found that the adsorption of As(III) was exothermic, whereas As(V) adsorption was endothermic.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Arsenic adsorption; Activation of red mud; Langmuir isotherm